The Concept of Effective Resolution of Divorce Cases in Reducing Divorce Rates at the Religious Court and Supreme Court Levels - Herlina, Herlina (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2026)
The phenomenon of domestic conflicts culminating in divorce litigation in Indonesia reflects complex normative and procedural dynamics, particularly when cases proceed to the Supreme Court and require an exceptionally prolonged period for final adjudication. This study examines the factors contributing to the protracted duration of divorce rulings and formulates an effective conceptual framework for resolving sustained marital conflicts within the judicial process. The analysis focuses on the practice of religious courts and the lived experiences of disputing parties whose cases extend over several years. This research is grounded in fieldwork conducted in Palembang, involving clients of the Herlina Herman Beroni Family and Sharia Consulting Institute as key informants. Data were collected through in-depth interviews and case document analysis, and were examined qualitatively using a normative juridical approach. Data collection and analysis were conducted concurrently until saturation was achieved. The findings indicate that the prolonged settlement of divorce cases is not merely the result of procedural complexity within the judicial system, but is deeply influenced by persistent interpersonal conflict, breakdowns in communication between spouses, adversarial litigation strategies, and the absence of effective conflict de-escalation mechanisms at earlier stages of the process. These conditions generate stagnation within religious court practice and contribute to extended adjudication timelines, particularly when cases escalate to higher judicial levels. The study argues that effective divorce resolution requires a paradigm shift from a predominantly formalistic litigation model toward a more integrative framework that prioritizes substantive conflict resolution, structured mediation, and communicative restoration between parties. The implications of this research underscore the necessity for institutional reform within religious courts, including the strengthening of mediation mechanisms, the integration of socio-psychological counseling into judicial procedures, and the development of regulatory policies that prevent procedural delays. By bridging normative legal analysis with empirical realities, this study contributes to broader discussions on judicial efficiency, access to justice, and the contextual adaptation of Islamic family law within contemporary Indonesian legal practice. [Fenomena konflik rumah tangga yang berujung pada litigasi perceraian di Indonesia mencerminkan dinamika normatif dan prosedural yang kompleks, khususnya ketika perkara tersebut berlanjut hingga tingkat Mahkamah Agung dan memerlukan waktu yang sangat panjang untuk memperoleh putusan berkekuatan hukum tetap. Penelitian ini menganalisis faktor-faktor yang menyebabkan lamanya penyelesaian perkara perceraian serta merumuskan kerangka konseptual yang efektif untuk menangani konflik perkawinan yang berkepanjangan dalam proses peradilan. Kajian ini memusatkan perhatian pada praktik peradilan agama serta pengalaman empiris para pihak yang terlibat dalam sengketa rumah tangga yang berlangsung selama bertahun-tahun. Penelitian ini didasarkan pada studi lapangan yang dilakukan di Kota Palembang dengan melibatkan klien Lembaga Konsultasi Keluarga dan Syariah Herlina Herman Beroni sebagai informan kunci. Data dikumpulkan melalui wawancara mendalam dan analisis dokumen perkara, kemudian dianalisis secara kualitatif menggunakan pendekatan yuridis normatif. Proses pengumpulan dan analisis data dilakukan secara simultan hingga mencapai kejenuhan data. Hasil penelitian menunjukkan bahwa lamanya penyelesaian perkara perceraian tidak semata-mata disebabkan oleh kompleksitas prosedural dalam sistem peradilan, tetapi juga dipengaruhi oleh konflik interpersonal yang terus berlanjut, terputusnya komunikasi antara suami dan istri, strategi litigasi yang bersifat konfrontatif, serta belum optimalnya mekanisme de-eskalasi konflik pada tahap awal penyelesaian perkara. Kondisi tersebut menimbulkan stagnasi dalam praktik peradilan agama dan berkontribusi pada panjangnya proses adjudikasi, terutama ketika perkara meningkat ke tingkat peradilan yang lebih tinggi. Penelitian ini menegaskan bahwa penyelesaian perceraian yang efektif memerlukan pergeseran paradigma dari model litigasi yang formalistik menuju kerangka yang lebih integratif dengan menekankan resolusi konflik substantif, mediasi yang terstruktur, serta pemulihan komunikasi antara para pihak. Implikasi penelitian ini menunjukkan urgensi reformasi kelembagaan dalam peradilan agama, termasuk penguatan mekanisme mediasi, integrasi layanan konseling sosial-psikologis dalam prosedur peradilan, serta pengembangan kebijakan regulatif yang mampu mencegah terjadinya penundaan proses hukum. Dengan menghubungkan analisis normatif dengan realitas empiris, penelitian ini berkontribusi pada perdebatan yang lebih luas mengenai efisiensi peradilan, akses terhadap keadilan, serta adaptasi kontekstual hukum keluarga Islam dalam praktik hukum Indonesia kontemporer.